STeP into Science Project: Engaging Students, Teachers and Parents in Debates - Kelly, R; Erduran, S; Walshe, G; Guilfoyle, L (Dublin City University, 2016)
This project aims to facilitate the teaching and learning of Irish lower second-level curricular objectives on Nature of Science, through engaging teachers, students and guardians in school debate events on socio-scientific issues. The Junior Cycle science specification promotes skills such as communication and argumentation which are also required for engaging in debates. Yet the kinds of pedagogical strategies demanded by debates are not typically part of teaching practice (Osborne, Erduran and Simon 2004). The first stage of this project therefore is CPD supporting science teachers to implement argumentation into their teaching of science in order to provide students with a foundation for the kinds of skills they need to draw on when debating scientific issues. Argumentation has been a significant area of research in recent years (Erduran, Ozdem and Park, 2015) and has been advocated in science teacher education (Erduran, 2006). The teachers involved will subsequently implement argumentation activities into their teaching and coordinate a debate event in autumn 2016. Involving the community in school science is a critical element of this project. Hence students will prepare for their debate event with the support and involvement of a family member with targeted homework activities, provided to teachers during the CPD workshop. Evaluation instruments will be used to assess (i) teacher perspectives on the CPD and (ii) teacher, student and guardian perspectives on participation in debates. This paper will outline the overall design of the project and report on initial findings from the teachers’ evaluation of the CPD element of the programme.